Influence of Functional Convenience, Celebrity Endorsment, and Self-Esteem on Impulsion Purchasing : Study on Somethinc Product Consumers in Semarang City - Maydista Lestari; Endang Sulistiyani; Rif'ah Dwi Astuti (JOBS (Jurnal Of Business Studies), 2024)
This study was conducted to determine the effect of Functional Convenience, Celebrity Endorsment, and Self-Esteem on Impulsive Buying studies on consumers of Somethinc products in Semarang City. The independent variables used are Functional Convenience (X1), Celebrity Endorsment (X2), and Self-Esteem (X3), while Impulsive Buying (Y) is the dependent variable. This study involved 162 respondents as a sample of Somethinc product consumers in Semarang City. Nonprobability sampling method focusing on purposive sampling was applied to select samples with the criteria of having used Somethinc products for themselves. Questionnaires, literature review, and interviews were used for data collection. The majority of respondents were women aged 21 to 25 years old who were students with an income of <Rp 2,000,000. Data were analyzed using the statistical testing program SPSS 27.0. Multiple linear regression analysis resulted in the equation Y = 20.396α + 0.555X1 + 0.084X2 + 0.132X3 + e. Data were analyzed using the SPSS 27.0 statistical testing program. The findings of this study suggest that Functional Convenience has a significant effect on Impulsive Buying, then Self-Esteem also has a significant effect on Impulsive Buying, then Celebrity Endorsment has no effect on Impulsive Buying. The coefficient of determination results in the effect of Functional Convenience, Celebrity Endorsment, and Self-Esteem of 47.1% on Impulsive Buying, while the other 52.9% is a variable not examined in this research model. Penelitian ini dilaksanakan guna mengetahui pengaruh Kenyamanan Fungsional, Dukungan Selebriti, dan Self-Esteem terhadap Pembelian Impulsif studi pada konsumen produk Somethinc di Kota Semarang. Variabel independen yang digunakan adalah Kenyamanan Fungsional (KF), Dukungan Selebriti (DS), dan Self-Esteem (SE), sedangakan Pembelian Impulsif (PI) sebagai variabel dependen. Penelitian ini melibatkan 162 responden sebagai sampel konsumen produk Somethinc di Kota Semarang. Metode nonprobability sampling yang berfokus pada purposive sampling diterapkan guna memilih sampel yang berkriteria telah memakai produk Somethinc untuk diri sendiri. Kuesioner, studi Pustaka, dan wawancara dipergunakan guna pengumpulan data. Mayoritas responden ialah perempuan berusia 21 hingga 25 tahun yang merupakan pelajar/mahasiswa dengan penghasilan < Rp 2.000.000. Data analisis menggunakan program pengujian statistik SPSS 27.0. Analisis regresi linear berganda menghsilkan persamaan Y = 20,396α + 0,555X1 + 0,084X2 + 0,132X3 + e. Temuan penelitian ini mengemukakan Kenyamanan Fungsional berpengaruh signifikan pada Pembelian Impulsif, selanjutnya Self-Esteem juga berpengaruh signifikan pada Pembelian Impulsif, kemudian Dukungan Selebriti tidak berpengaruh pada Pembelian Impulsif. Hasil koefisien determinasi menghasilkan pengaruh Kenyamanan Fungsional, Dukungan Selebriti, dan Self-Esteem sebesar 47,1% pada Pembelian Impulsif, sementara 52,9% lainnya merupakan variabel yang tidak diteliti pada model penelitian ini.